NUMERICAL SOLUTION OF THIN FILM EQUATION IN A CLASS OF DISCONTINUOUS FUNCTIONS - Sinsoysal, Bahaddin; Rasulov, Mahir (European Scientific Journal, ESJ, 2015)
In this paper, an original method has been suggested to find a numerical solution of initial value problem for a fourth order degenerate diffusion equation which models the thin film flow. For this, an auxiliary problem established in a special way and having some advantages over the main problem has been introduced. Advantages of the auxiliary problem allow us to apply one of the well-known methods in literature, and thus the numerical solution of the main problem can be calculated by using the obtained solution.